Diagnostics of Linear Systems in the State Space - Verlan A. F.; Polozhaenko S. A. (Problems of the Regional Energetics)
The analysis of the state of the problem of quality ensurance and proper functioning of electri-cal systems and devices was carried out. It showed that not only the complete feasibility of monitoring their performance at the production and operation stages should be considered, but also the potential diagnostics of the systems and devices being developed should be ensured. At the same time, the limitations of the existing methodological support for conducting diag-nostic experiments were noted. It was indicated that a possible solution of this problem was to use for diagnosing at all stages of the life cycle (in particular, designing, manufacturing and operating) the controlled systems and model-oriented methods, which made it possible to fill up a measurement information deficiency during the simulation of their schemes using the ap-propriate models. The purpose of this research was to further develop the model-oriented methods for diagnosis of the technical state of the electrical systems and devices, which was achieved by formalizing the task and developing constructive algorithms for localization of faulty subsystems in the state space. In this context, a method for the diagnostics of the linear systems (devices) was proposed, which ensures testing of the working hypotheses by describ-ing them (the essence is the representation of the model) in the state space. Unlike the existing ones, the method allowed us, when conducting a diagnostic experiment, to avoid measuring the potentials at the nodes of the selected (localized) subcircuits. The application possibilities of the method in the engineering practice were illustrated by examples.